About some aspects of influence on the activities of political parties in the Russian Federation - M. Y. Dityatkovsky; I. S. Kurskiy (Правоприменение, 2025)
This article examines the issues of influencing the activities of political parties through the entry of political parties into coalitions, their international interaction, as well as obtaining funding. The paper provides an analysis of federal legislation governing the implementation of the right of political parties to unite, international relations and receive funding, and proposes new mechanisms for monitoring the implementation of the first two of the abovementioned rights. In this paper, we have considered three potential ways to influence the activities of political parties in the Russian Federation: through the exercise of the right of a political party to a coalition, through the exercise of the right to international relations, as well as direct financing of the activities of political parties.We found out that today in the Russian Federation there is a mechanism to protect against interference in the activities of political parties in the field of their financing, but there is no mechanism to protect against potential influence on political parties from other political parties, public associations, including foreign ones, as well as international unions and associations As a mechanism for monitoring the implementation of interaction between political parties and other public associations, the preliminary and subsequent control of their relations by the Ministry of Justice of the Russian Federation is proposed.Also, as a proportionate means of controlling coalition associations of political parties, it is proposed to establish a ban on the creation of associations and unions with other political parties and other public associations without forming a legal entity in the case when they are persons recognized as foreign agents.